2023
DOI: 10.2174/18744346-v17-230720-2023-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Health-promoting Lifestyle Profile among Menopausal Women: A Meta-analysis

Abstract: Background: Menopause is one of the most drastic experiences in a woman's life because of a spectrum of vasomotor symptoms which affect the quality of life and lifestyle. Although many treatments for these symptoms are available, they can be used for only a short duration. The nonpharmacologic therapies associated with healthy lifestyle behaviors are increasing. Health-Promoting Lifestyle Profile- II (HPLP-II), a self-report questionnaire designed to assess an individual's engagement in health-promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In addition, a statistically significant difference between the control and the intervention groups in the total score of health promotion behaviours and its subscales was reported, indicating the effectiveness of such educational programs. Furthermore, a meta-analysis study conducted by Moshfeghy, Riazi, Hajian, & Montazeri, (2023) (35) revealed that following the intervention, the intervention group's mean score of the health-promoting lifestyle was significantly higher compared to the control group. Additionally, Chafjiri1 et al, 2018 (36) came to the conclusion that educational programs are crucial in incorporating a healthy lifestyle to motivate older adults to take greater responsibility for their health, continued physical fitness, a balanced diet, positive interpersonal relationships, anticipated spiritual growth, and effective stress and anxiety management.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a statistically significant difference between the control and the intervention groups in the total score of health promotion behaviours and its subscales was reported, indicating the effectiveness of such educational programs. Furthermore, a meta-analysis study conducted by Moshfeghy, Riazi, Hajian, & Montazeri, (2023) (35) revealed that following the intervention, the intervention group's mean score of the health-promoting lifestyle was significantly higher compared to the control group. Additionally, Chafjiri1 et al, 2018 (36) came to the conclusion that educational programs are crucial in incorporating a healthy lifestyle to motivate older adults to take greater responsibility for their health, continued physical fitness, a balanced diet, positive interpersonal relationships, anticipated spiritual growth, and effective stress and anxiety management.…”
Section: Discussionmentioning
confidence: 99%